Current status of functional and multifunctional materials for 3D microfabrication: An overview. (25th January 2020) - Young, Brandon D.; Gamboa, Bryan; Bhalla, Amar S.; Guo, Ruyan
Abstract: 3D printing is among the most exciting and rapidly advancing fields of research in materials engineering and device fabrication. The capability of developing a bottom-up approach to device fabrication, which eliminates wasted material and the need for complex environmental conditions, is of incredible interest to researchers. The most critical factor in the success of this technology is the development of suitable materials and inks which facilitate the fabrication of the designed functional geometry. Printing of materials on the macroscale and microscale is ultimately simpler and researchers encounter fewer problems in achieving their intended goals. As the printing technologies lead to the micron and submicron scales, the requirements for printing invariably become increasingly stringent and more difficult to overcome. In the past decade or so researchers have tried to develop suitable inks for the development of nanoscale printing of functional electronic materials, with some or little success. Current 3D deposition approaches are leading to successful nanoscale printing of micron/submicron scale functional and multifunctional materials and devices. In this context, this article provides an overview of currently utilized deposition techniques, along with presentations and analyses of successfully formulated and deposited conductive, dielectric, and magnetic inks by researchers in the field.